Low voltage water electrolysis: Decoupling hydrogen production using bioelectrochemical system. (9th August 2018) - Belleville, Pierre; Guillet, Francois; Pons, Alessia; Deseure, Jonathan; Merlin, Gérard; Druart, Florence; Ramousse, Julien; Grindler, Elisa
Abstract: Decoupling water electrolysis using mediator is an interesting way to produce pure hydrogen. The present work validates the proof of concept of decoupled electrolyser associated with a bioelectrochemical system (MFC-DES) through a redox flow mediator (potassium hexacyanoferrate (KHCF)). Low voltage (1 V) hydrogen production was achieved with a current density up to 25 mA cm −2 . Regeneration of the mediator was performed by glucose fed microbial fuel cells. The oxidation rate of KHCF in the electrolyser is, at least, an order of magnitude higher than the reduction rate in MFC cascade fed system. MFC-DES is thus a promising set up as it desynchronizes limited microbial rate and hydrogen production, generate value from wastewater and reduce energetic cost of water electrolysis. Graphical abstract: Image 1 Highlights: Proof of concept of hydrogen generation coupling Electrolyser with MFC device. Hydrogen production with only 1 V of cell voltage. Overpass performance of direct hydrogen production with MEC. Mediator management in close loop overcomes oxygen reaction limitation.